The Correlation Between Adversity Quotient and Self-Regulated Learning of Official Students at Forestry - Rolyadin Siboro, Eliakim (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The study was conducted based on the researcher's interest in the condition of students in learning, where the Pekanbaru forestry vocational high school is one of 5 forestry vocational schools in Indonesia under the Ministry of Environment and Forestry of the Republic of Indonesia, which has different rules and ways of educating from schools in general. High demands on school quality standards require students to condition themselves and their minds in a pressure both in managing time and the very monotonous environment faced by students, aiming to achieve an achievement and good results. Based on these problems, this study was conducted with a quantitative research method that uses a scale as a measuring tool for collecting research data. The population in this study were all students of Forestry Vocational High School Pekanbaru, the total sample was 209 students of class X and XI which were determined by purposive random sampling technique. Based on the results of data analysis using product moment correlation analysis techniques with a correlation coefficient (r) of (0.695) with a significant (p) of (0.000) (p <0.01), the magnitude of the variable contribution value (R squared) 48.3%. So it is concluded that the hypothesis in this study is accepted, with the explanation that there is a positive and significant relationship between adversity quotient and self-regulated learning in Pekanbaru Forestry Vocational High School students.